The Legal Relevance of Labor Protection within the Framework of Positive Law in Indonesia - Zahara, Naurah Al; Prayitno, Vito Rekso; Permana, Deni Yusup; Ghaffar , Zelfi (PT FORMOSA CENDEKIA GLOBAL, 2025)
Labor encompasses all individuals capable of performing work to generate commodities or services, fulfilling both personal and communal needs. Derived from the Equality Before the Law principle, which asserts that all individuals possess the right to equitable legal recognition, protection, assurance, and certainty, as well as uniform treatment under the law, this constitutes the foundation of legal equality. This study evaluates the efficacy of legal frameworks in safeguarding the rights of employees subjected to Termination of Employment (PHK) owing to extended illness, by scrutinizing the types of legal protections afforded to them. Methods. The employed methodology is doctrinal normative legal research, utilizing a legislative approach with pertinent case studies, regulatory examination, judicial rulings, and perspectives from legal scholars. Result. The study's results indicate that violations persist in practice, notwithstanding the provisions in Law Number 6 of 2023 about Job Creation that safeguard workers dismissed due to extended illness. This circumstance indicates that legal rules alone are insufficient. Consequently, the government must enhance ongoing oversight and elevate legal awareness among workers and employers to ensure adherence to established standards.